On the works of the Dokuchaev Soil Science Institute in Uzbekistan - E. I. Pankova; I. A. Yamnova; L. F. Nazarova; D. A. Soloviev; V. A. Isaev (Бюллетень Почвенного института им. В.В. Докучаева, 2022)
The article considers the history of the work of the Dokuchaev Soil Science Institute researchers in Uzbekistan, conducted jointly with soil scientists from Uzbekistan. These works were started in 1930–1940s. They were especially active during the Great Patriotic War, when the Soil Institute was evacuated to Tashkent. During these years, both Russian and Uzbek soil scientists participated in joint work. Outstanding scientists can be named among Russian researchers: V.A. Kovda, A.A. Rode, A.N. Rozanov and many others who contributed to the study of Uzbekistan soils. The work of the researchers from the Dokuchaev Soil Science Institute, performed on the basis of a station in the Hungry Steppe (Mirzacho'l) in connection with the development of saline lands during the creation of new irrigation systems in Central Asia, is analyzed in particular detail. Various work areas of the station researchers are discussed in the article: issues of ameliorative development of saline soils, salinity mapping based on remote sensing methods, detailed study of the reclaimed soils properties using chemical, micromorphological, mineralogical and other research methods for the determination of salinity and gypsum content of soils in the New Irrigation Zone (NIZ) of Hungry and Jizzakh steppes. The results of the work were presented in a series of publications. In the 1990s, cooperation was temporarily ceased, but at the beginning of the 21st century it was resumed.